(untitled) (Bangladesh Journal of Anatomy, 2018)
Introduction: Plastination is a modern method of body preservation. The plastinated specimens are dry, odourless, highly durable, non-toxic, non-infectious. As various factors may contribute to the determination of the quality of the plastinates, this research is designed to find out the influence of one factor such as temperature on the plastinates. Objectives: The study was done to compare the percentage of gross shrinkages by volume of pig hearts in different stages of silicone (S10) plastination at cold temperature with those at room temperature. Materials and Methods:. This experimental study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University, Dhaka on twenty-four pig hearts. The percentages of gross shrinkages by volume were calculated for different stages of plastination at cold temperature and at room temperature. Results: The overall mean percentage of gross shrinkage by volume of the pig hearts was significantly greater (38.01±18.78) in cold temperature group than in room temperature group (26.50±12.63). Conclusions: The present study showed the quality of plastinates is better in room temperature than in cold temperature. Thus, room temperature procedure is suitable for our country and also cost-effective which fulfill the ever-increasing demands of user-friendly anatomical tools for the teachers and learners. Bangladesh Journal of Anatomy January 2018, Vol. 16, No. 1, pp. 21-24